An Irish-Jewish Politician, Joyce's Dublin, and Ulysses : The Life and Times of Albert L. Altman. - Davison, Neil R. (University Press of Florida, 2022)
In this book, Neil Davison argues that Albert Altman, aDublin-based businessman and Irish nationalist, influenced James Joyce'screation of the character of Leopold Bloom as well as Ulysses' broaderthemes surrounding race, nationalism, and empire.
Description based upon print version of record.
Keywords: Joyce, James, -- 1882-1941. -- Ulysses.; Bloom, Leopold -- (Fictitious character); Altman, Albert L. -- 1853-1903.; Ulysses (Joyce, James); Jews in literature.; Jews in public life -- Ireland -- Dublin -- Biography.; Jews -- Ireland -- Dublin -- Biography.; Jewish politicians -- Ireland -- Dublin -- Biography.; Juifs dans la littérature.; Juifs dans la vie publique -- Irlande -- Dublin -- Biographies.; Juifs -- Irlande -- Dublin -- Biographies.; LITERARY CRITICISM / Modern / 20th Century.; LITERARY CRITICISM / Subjects & Themes / Historical Events.; Jews in public life; Jews in literature; Jews; Jewish politicians; Ireland -- Dublin; Biographies